Basic modern theoretical approaches to study the deviant behavior among youth - Kozak, Ihor (Journal of Education, Health and Sport, 2016)
The article presented discusses the concept of deviant behavior with different philosophical, social and psychological concepts in different historical periods. It is determined that Ukrainian society is today in a state of value-normative disintegration, that is, social anemia. The idea of anemia belongs to E. Durkheim - this is a social condition, which is characterized by the decomposition of the value system caused by the crisis of the whole society, its social institutions, the contradiction between the declared goals and the impossibility of their realization for the majority. In the modern period, the “old norms” are no longer relevant, and the new norms are emerging and are still very vague and unclearly formulated to serve as effective and meaningful benchmarks in behavior. Therefore, it is in the modern periods that a sharp increase in the number of cases of deviation can be expected. Due to the analysis of philosophical, sociological, psychological and psychological-pedagogical literature covering the concept of deviant behavior. It has been established that despite the existence of a set of concepts of deviance of one concept, which would fully cover all the determinants and forms of deviant behavior of young people, it has not yet been created.